Identification and molecular characterization of a novel 163 kb deletion: The Italian (ϵγδβ)0-thalassemia. Issue 5 (27th May 2016) - Cardiero, Giovanna; Prezioso, Romeo; Dembech, Sabrina; Del Vecchio Blanco, Francesca; Scarano, Clelia; Lacerra, Giuseppina
Abstract : Objective and importance : To verify the presence of β-thalassemia in subjects showing hematologic phenotype of α-thalassemia, conduct normal molecular sequence analysis of the α-globin genes, and detect the absence of the most frequent α-thalassemia deletions. Clinical presentation: A patient from Apulia (Southern Italy) was referred to our institution for the occasional founding of hypochromic polyglobulia and microcytic red blood cells associated with normal levels of Hb A2 and Hb F and normal iron parameters. Intervention and technique : The patient has been investigated using Sanger sequencing, multiplex ligation-dependent probe amplification (MLPA), quantitative real-time PCR, restriction analysis, and gap-PCR. A novel deletion, the Italian (ϵγδβ) 0 -thalassemia, has been identified. The 5′ breakpoint was within a LINE element of 80 kb 3′ of the ε-globin gene, and the 3′ breakpoint was within a 160-bp palindrome of about 30 kb 5′ of the β-globin gene. The breakpoint region was characterized by the presence of a microhomology (5′-TCT-3′) and of an insertion of 43 bp owing to the duplication of the 160-bp palindrome. Comparison of the Hb and Hb A2 values of (ϵγδβ) 0 -thalassemia from the literature with those of (molecularly known) thalassemia carriers indicated a higher level of Hb A2 with respect to α-thalassemia and a lower level of Hb with respect to β 0 -thalassemia carriers. Conclusion : In this study, we report the first (ϵγδβ) 0 -thalassemia case identified in Italy. To avoid misdiagnosis of β-thalassemia, we suggest verifying the presence of large deletions of the β-globin gene cluster in subjects showing a higher border line level of Hb A2 and a lower level of Hb.